Controversy Surrounding the Function of SpiC Protein in Salmonella: An Overview - Wang, Yaonan; Cai, Yuan; Zhang, Jian; Liu, Dong; Gong, Xiao; Pan, Zhiming; Geng, Shizhong; Jiao, Xin’an (Frontiers in Microbiology, 2019)
Salmonella is an important pathogenic microorganism that can infect humans and animals and has been widely studied globally as a model microorganism for its pathogenesis. The SpiC protein of T3SS2 is an important factor that has been studied for over twenty years, but to date, the function of SpiC in the pathogenesis of Salmonella has not been completely understood. There is controversy over the functions of the SpiC protein in the literature. Thus, an overview of the literature on the SpiC protein is provided herein for future studies.